2010
DOI: 10.26719/2010.16.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-incidence analysis of government spending on Ministry of Health outpatient services in Jordan

Abstract: A benefit-incidence analysis was conducted for the year 2000 using various data sources including the Jordan healthcare utilization and expenditure survey 2000. The results illustrate that the poorest segment of the Jordanian population were the most likely to report sickness and seek treatment and were the main users of the Ministry of Health outpatient services. The poorest uninsured individuals were the main source of revenues generated through user fees. The targeting efficiency (i.e. total percentage of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 2 publications
0
14
1
Order By: Relevance
“…The burden of OOP expenditures may be a major contributor to the inequity in GHS benefit distribution. High user fees decrease healthcare utilization, and the poor who need medical services but cannot afford them will be excluded from the benefits [ 34 ]. We found that OOP expenditures for outpatient care decreased from 2002 to 2007 in both urban and rural areas, while inpatient expenditures increased in urban areas and remained almost unchanged in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of OOP expenditures may be a major contributor to the inequity in GHS benefit distribution. High user fees decrease healthcare utilization, and the poor who need medical services but cannot afford them will be excluded from the benefits [ 34 ]. We found that OOP expenditures for outpatient care decreased from 2002 to 2007 in both urban and rural areas, while inpatient expenditures increased in urban areas and remained almost unchanged in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature has demonstrated that better-off individuals receive more public health subsidies than the poor in many Asian countries and regions that rely heavily on out-of-pocket (OOP) payment. Researchers have also suggested that the poor receive fewer subsidies because they simply cannot afford to pay and so forego treatment [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, BIA is the net government subsidy weighted by the utilization rate [17,18]. Mathematically, the BIA could be estimated by the formula -Specifically, is number of aged people from a particular MPCE class (j) who are suffering from NCDs and utilizing the public healthcare facilities.…”
Section: Benefit Incidence Analysismentioning
confidence: 99%